Magnetotransport in C-doped AlGaAs heterostructures - Grbić, B.; Ellenberger, C.; Ihn, T.; Ensslin, K.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Magnetic-field-induced excitons in photoluminescence from heavily doped p-type Ga1−xAlxAs/GaAs single heterojunction - Bryja, L.; Kubisa, M.; Ryczko, K.; Misiewicz, J.; Stȩpniewski, R.; Byszewski, M.; Potemski, M.; Reuter, Dirk; Wieck, A. (Physica B: Condensed Matter)

In-plane gate transistors in AlxGa1−xN/GaN heterostructures written by focused ion beams - Ebbers, A.; Reuter, Dirk; Heuken, M.; Wieck, A.D. (Superlattices and Microstructures)

New Britain as Consumer Country and Commodity - Tönnies, Merle (Journal for the Study of British Cultures)

Wirtschaftspädagogische Sichtweise der Spannungsverhältnisse in der Lehrerbildung vor dem Hintergrund des Lernfeldansatzes unter Berücksichtigung des Komplementärprinzips - Beutner, Marc; Twardy, M (Aktuelle Aspekte in Schule und wissenschaftlichem Unterricht. Studien und Berichte des IWP)

Ein Determinantenmodell der Ausbildungsbereitschaft von Klein- und Mittelbetrieben – Basis für eine systematische Förderung der Berufsausbildung - Beutner, Marc (Zukunft der Berufsausbildung in Deutschland: Empirische Untersuchungen und Schlussfolgerungen. Berichte zur Beruflichen Bildung 273)

Mergenthal, S.: A Fast-Forward Version of England, 2003 - Tönnies, Merle (Anglia)

Ambient Networks--Research for Communication Networks Beyond 3G - Niebert, Norbert; Flinck, Hannu; Hancock, Robert; Karl, Holger; Prehofer, Christian (13th IST Mobile and Wireless Communications-Summit 2004)

Throughput study for a dynamic OFDM-FDMA system with inband signaling - Gross, James; Paoluzzi, Irene; Karl, Holger; Wolisz, Adam (Vehicular Technology Conference, 2004. VTC 2004-Spring. 2004 IEEE 59th)

A hybrid approach for location-based service discovery in vehicular ad hoc networks - Klimin, Nikolay; Enkelmann, Wilfried; Karl, Holger; Wolisz, Adam (Proc. of WIT)

Distributed allocation of time slots for real-time traffic in a wireless multi-hop network - Carlson, Emma; Karl, Holger; Wolisz, Adam; Prehofer, Christian (Proc. European Wireless)

Capacity increase of multi-hop cellular wlans exploiting data rate adaptation and frequency recycling - Mengesha, Seble; Karl, Holger; Wolisz, Adam (Proc. of MedHocNet 2004)

Evolutionary equilibrium in Tullock contests: spite and overdissipation - Hehenkamp, Burkhard; Leininger, W.; Possajennikov, A. (European Journal of Political Economy)

Adiabatically driven electron dynamics in a resonant photonic band gap: Optical switching of a Bragg periodic semiconductor - Schaarschmidt, Martin; Förstner, Jens; Knorr, Andreas; Prineas, John P.; Nielsen, Nils C.; Kuhl, Jürgen; Khitrova, Galina; Gibbs, Hyatt M.; Giessen, Harald; Koch, Stephan W. (Physical Review B)
The adiabatic driving of the resonant electron dynamics in a one-dimensional resonant photonic band gap is proposed as an optical mechanism for nonlinear ultrafast switching. Pulsed excitation inside the photonic gap results in an ultrafast suppression and recovery of the gap. This behavior results from the adiabatic carrier dynamics due to rapid radiative damping inside the band gap.
Keywords: tet_topic_qw

Polaron signatures in the line shape of semiconductor ;intersubband transitions: quantum kinetics of the electron–phonon interaction - Butscher, S.; Förstner, Jens; Waldmüller, I.; Knorr, A. (physica status solidi (b))
We present a theory of the optical line shape of coherent intersubband transitions in a semiconductor quantum well, considering non-Markovian LO-phonon scattering as major broadening mechanism. We show that a quantum kinetic approach leads to additional polaron resonances and a resonance enhancement for gap energies close to the phonon energy.
Keywords: tet_topic_qw

Linear and nonlinear pulse propagation in a multiple-quantum-well photonic crystal - Nielsen, N. C.; Kuhl, J.; Schaarschmidt, M.; Förstner, Jens; Knorr, A.; Koch, S. W.; Khitrova, G.; Gibbs, H. M.; Giessen, H. (Physical Review B)
We investigate the temporal and spectral properties of subpicosecond pulses transmitted on the heavy-hole exciton transition through a multiple-quantum-well Bragg structure, exhibiting a one-dimensional photonic band gap. At low light intensities, a temporal propagation beating is observed. This beating is strongly dependent on the optical dephasing time T2 which is dominated by the radiative interwell coupling. In an intermediate intensity regime, the Pauli-blocking nonlinearity leads to gradual suppression of the photonic band gap and vanishing of the linear propagation beating. For highly nonlinear excitation, we find signatures of selfinduced transmission due to Rabi flopping and adiabatic following of the carrier density. Numerical simulations using the semiconductor Maxwell-Bloch equations are in excellent agreement with the experimental data up to intensities for which higher many-particle correlations become more important and self-phase modulation occurs in the sample substrate.
Keywords: tet_topic_qw

Subpicosecond spatiotemporal pulse compression in a nonlinear defocusing material - Nielsen, Nils. C.; Siederdissen, Tilmann H. zu; Kuhl, Jürgen; Schaarschmidt, Martin; Förstner, Jens; Knorr, Andreas; Koch, Stephan W.; Giessen, Harald (International Conference on Ultrafast Phenomena 2004)
We demonstrate temporal and spatial pulse compression and modulational instabilities in the nonlinear defocusing regime near the band edge of bulk GaAs. Experiment and theory show that spatiotemporal coupling is responsible for these surprising phenomena.
Keywords: tet_topic_polariton

Temporal phase evolution during excitonic Rabi flopping in semiconductors - Höner zu Siederdissen, Tilman; Nielsen, Nils Christian.; Kuhl, Jürgen; Förstner, Jens; Knorr, Andreas; Giessen, Harald (International Quantum Electronics Conference and Photonic Applications Systems Technologies)
Theoretically and experimentally, we investigate temporal phase evolution during Rabi-flopping on the A-exciton resonance in CdSe using a novel fast-scanning XFROG method and observe phase changes smaller than π/2 compared to the slightly-chirped input pulse.
Keywords: tet_topic_qd

Temporal and spatial compression of near-resonant pulses in a nonlinear defocusing semiconductor - Nielsen, Nils C.; Kuhl, Jürgen; Schaarschmidt, Martin; Förstner, Jens; Knorr, Andreas; Koch, Stephan W.; Giessen, Harald (Conference on Lasers and Electro-Optics/International Quantum Electronics Conference and Photonic Applications Systems Technologies)
The coupled spatiotemporal characteristics of subpicosecond pulses propagating in the nonlinear defocusing regime near the band edge of bulk GaAs are investigated experimentally and theoretically. We demonstrate pulse compression both in time and transverse space.
Keywords: tet_topic_polariton

Nonlinear light pulse propagation in Bragg-periodic multiple semiconductor quantum well samples: ultrafast switching of a resonant photonic band gap - Schaarschmidt, Martin; Förstner, Jens; Knorr, Andreas; Prineas, John P.; Nielsen, Nils C.; Kuhl, Jürgen; Kithrova, Galina; Gibbs, Hyatt M.; Giessen, Harald; Koch, Stephan W. (Conference on Lasers and Electro-Optics/International Quantum Electronics Conference and Photonic Applications Systems Technologies)
We investigate theoretically the ultrafast nonlinear suppression of the resonant photonic band gap by strong laser pulses in semiconductor multiple qnantum wells. We achieve good agreement with our measurements on reflection samples.
Keywords: tet_topic_qw